2009
DOI: 10.1200/jco.2009.27.15_suppl.6041
|View full text |Cite
|
Sign up to set email alerts
|

A phase IIb 4-arm open-label randomized study to assess the safety and efficacy of h-R3 monoclonal antibody against EGFR in combination with chemoradiation therapy or radiation therapy in patients with advanced (stage III or IVA) inoperable head and neck cancer

Abstract: 6041 Background: Patients (pt) with advanced inoperable squamous cell carcinoma of the head and neck (SCCHN) have poor radiotherapy alone (RT) outcome. EGFR is over-expressed in >90% SCCHN. h-R3mAb (BIOMAb/nimotuzumab/TheraCIM) is a humanized monoclonal antibody, a validated oncotherapeutic-targeting EGFR. Objective: To investigate the safety and efficacy of concurrent h-R3mAb in combination with chemoradiotherapy of SCCHN. Methods: September 2004–2005, pt 18–70 yrs, SCCHN stageIII-IVA, 113 screened, 92 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A retrospective study of 835 patients with advanced carcinomas of diverse tissue types suggested that nimotuzumab was well tolerated in combination with CRT, without potentiating the toxicities of concurrent therapy [42]. Randomized phase II data demonstrated that nimotuzumab plus CRT improved median OS compared with RT alone [25,28]. Similarly, sequential lapatinib and RT yielded improvements in ORR compared with placebo/ RT (70% vs. 53%) in the definitive setting [26].…”
Section: Definitive Therapy For Unresectable Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of 835 patients with advanced carcinomas of diverse tissue types suggested that nimotuzumab was well tolerated in combination with CRT, without potentiating the toxicities of concurrent therapy [42]. Randomized phase II data demonstrated that nimotuzumab plus CRT improved median OS compared with RT alone [25,28]. Similarly, sequential lapatinib and RT yielded improvements in ORR compared with placebo/ RT (70% vs. 53%) in the definitive setting [26].…”
Section: Definitive Therapy For Unresectable Diseasementioning
confidence: 99%
“…Analyses of outcomes among patients with HPV-and non-HPV-associated disease The Oncologist ® treated with RT/platinum/EGFRI have been mixed [17,27]. Of interest, the addition of nimotuzumab to conventional RT/ cisplatin appears to improve the CR rate (96% vs. 72%) [29] and 30-month OS (70% vs. 22%) [25] but does not appear to potentiate the toxicity of CRT compared with RT/cisplatin alone [25,29,32,35,38].…”
Section: Definitive Therapy For Unresectable Diseasementioning
confidence: 99%